2017
DOI: 10.1257/aer.20141524
|View full text |Cite
|
Sign up to set email alerts
|

Eponymous Entrepreneurs

Abstract: We demonstrate that eponymy-firms being named after their owners-is linked to superior firm performance, but is relatively uncommon (about 19 percent of firms in our data). We propose an explanation based on eponymy creating an association between the entrepreneur and her firm that increases the reputational benefits/costs of successful/unsuccessful outcomes. We develop a corresponding signaling model, which further predicts that these effects will be stronger for entrepreneurs with rarer names. We find suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 29 publications
4
76
1
Order By: Relevance
“…Deephouse and Jaskiewicz (2013) found, for example, that PFFs owe their good reputations to the ambassadorial roles family members take up in them. Moreover, Belenzon, Chatterji, and Daley (2017) found that eponymy-the practice of firms being named after the families who own them-signals firm quality and ability. PFF leaders are also less likely to cause principalprincipal problems because they derive socioemotional wealth from preserving the family legacy (Deephouse & Jaskiewicz, 2013;Leitterstorf & Rau, 2014).…”
Section: Informal Constraining Institutions (Icis)mentioning
confidence: 99%
“…Deephouse and Jaskiewicz (2013) found, for example, that PFFs owe their good reputations to the ambassadorial roles family members take up in them. Moreover, Belenzon, Chatterji, and Daley (2017) found that eponymy-the practice of firms being named after the families who own them-signals firm quality and ability. PFF leaders are also less likely to cause principalprincipal problems because they derive socioemotional wealth from preserving the family legacy (Deephouse & Jaskiewicz, 2013;Leitterstorf & Rau, 2014).…”
Section: Informal Constraining Institutions (Icis)mentioning
confidence: 99%
“…We estimate outcomes on the basis of a small number of start-up characteristics: (i) firm name characteristics, including whether the firm name is eponymous [named after the founder ( 14)], is short or long, is associated with local business activity or regionally traded clusters (e.g., dry cleaning versus manufactured goods), or is associated with a set of high-technology industry clusters ( 15,16); (ii) how the firm is registered, including whether it is a corporation [rather than partnership or limited liability company (LLC)] and whether it is incorporated in Delaware ( 17); and (iii) whether the firm establishes control over formal intellectual property (IP) rights within 1 year of registration ( 18).…”
Section: Where Is Silicon Valley?mentioning
confidence: 99%
“…The choice of a firm's name is a deliberate process where the aim may be to inform consumers, for example, about the quality or price of the product (McDevitt, 2014) or to present a particular social identity (Belenzon et al, 2017). At the same time, according to Tadelis (1999), a firm is a "bearer of reputation".…”
Section: Introductionmentioning
confidence: 99%
“…Bach and Serrano-Velarde (2015) assumed that eponymous firms were family businesses and used the match between CEO surname and firm name to show that in eponymous firms, there is a stronger propensity to dynastic succession. In a recent study, Belenzon et al (2017) showed that eponymy is related to superior profitability as measured by the return on assets. The authors assume that eponymy creates a link between the founder and the firm, which results in reputational concerns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation